Technological equipment package for preparing polystyrene concrete mixture - Anishchenko, Anna; Blazko, Vladimir; Aleinikova, Alevtina; Salenko, Yulia (Academic journal Industrial Machine Building Civil Engineering, 2024)
The study of the production process for polystyrene concrete mixture products is driven by the need to ensure high material quality while meeting modern construction standards. To achieve this goal, an analytical method was used for reviewing literature sources, along with a design-calculation approach in the development of a new type of equipment. The main findings highlight the shortcomings of conventional concrete mixers, including extended mixing time, mixture non-uniformity, and material sticking to working surfaces. A novel design of a gravity-compelled cascade-type concrete mixer is proposed, featuring a horizontal ribbon-paddle shaft and a rotating drum. A key innovation is the ability to adjust the rotation modes depending on the mixture composition and the presence of sand. A compact equipment package was developed, comprising a mixer, fiber cutter, belt and screw feeders, all mounted on a single frame. The use of a belt feeder with synchronized component feeding and an automated fiber cutter ensures even distribution of reinforcing elements within the mixture. A methodology for determining the productivity of the unit has been developed, considering the mixer filling volume, the geometric parameters of working elements, and mixing process characteristics. Formulas were derived for selecting key parameters of the cutter and roller feed for the fiber bundle.The proposed equipment contributes to improved quality of polystyrene concrete, reduced energy consumption, and shorter production time. Future research will focus on optimizing operating modes of the equipment for different types of polystyrene concrete mixtures using fiber reinforcement.